Plate 17. View of Boppard - Janscha, Laurens, 1749-1812 (artist):::::::::::::::; Ziegler, Johann (engraver)::::::::::::::: (Edinburgh; Paul Harris; United Kingdom, 2020)
Color engraving with a panoramic view of the town of Boppart, on the Rhine River. Among the sights in this engraving are the Marienberg, a Benedictine abbey established in the 12th century.